The relationship between education and poverty in Israel - Ravit, Amar; Keren, Grinberg (IJRDO - Journal of Social Science and Humanities Research, 2016)
This article examines the strength of the relationship between education and poverty in Israel. The article shows that there is a reciprocal link between education and income. That is, in this generation, as the number of years of education of the person, the greater the average wage rises, Ktnim chances of being unemployed and Mtktzr time they need to reintegrate into the work force. The next generation, as the level of education and parental income will be higher, so will their children’s achievements. This link is strengthened by the positive correlation between socio-economic characteristics of communities and achievements Sltosbihm. In view of the importance of the issue indicates growth trends in the proportion and absolute sectors and population groups living in poverty reaking the generational cycle of great distress requires a change in education funding policy Education funding policy and allocation of resources for education in Israel today do not reduce the gaps between the various population groups, but perpetuate them, and sometimes even contribute to the expansion. Change is achieved by significantly increasing the resources allocated to disadvantaged population groups, by progressive allocation method. This method will contribute to reduce the debt of the interrelationship between poverty and education by reducing the gaps in academic performance by members of the various groups, and followed will lead to the reduction of future income disparities and reduce poverty levels in the population. This policy choice emphasizes the importance of education to national security, social cohesion and the location from a globalized world.